Vegetative Propagation of Acacia nilotica (L.) ssp. indica through Air-Iayering - Ahlawat, S. P.; Gupta, V. K.; Kumar, R V.; Datta, A. (Indian Journal of Agroforestry, 2020)
Effect of synthetic auxin IBA in inducing of rooting in Acacia nilotica ssp. indica was studied in the semi-arid region of central India. Secondary/ tertiary branches of 1-1.5 cm diameter on 5 to 20-years-old trees are used for air layering. Paste of different concentrations of IBA viz., 0, 1000, 1200, 1400, 1600, 1800 and 2000 ppm prepared in 3% agar was applied on girdled area of each branch during second week of August and September, respectively. Rooting percentage ranged from 80 to 85 in 1000 ppm and in 1000 to 1600 ppm treatments during August and September, respectively. Rooting was completed in 60Â±5 days. Survival rate of rooted air-layers varied from 67 to 100 per cent after two months of planting in polybags. These results and technique showed good potential in production of true to type elite plants for establishing the clonal seed orchards, gene banks and vegetative multiplication gardens.Â